2016
DOI: 10.1186/s12879-016-2009-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of smear microscopy and incremental yield of Xpert in detection of pulmonary tuberculosis in Rwanda

Abstract: BackgroundTuberculosis control program of Rwanda is currently phasing in light emitting diode-fluorescent microscopy (LED-FM) as an alternative to Ziehl-Neelsen (ZN) smear microscopy. This, alongside the newly introduced Xpert (Cepheid, Sunnyvale, CA, USA) is expected to improve diagnosis of tuberculosis and detection of rifampicin resistance in patients at health facilities. We assessed the accuracy of smear microscopy and the incremental sensitivity of Xpert at tuberculosis laboratories in Rwanda.MethodsThis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 19 publications
4
36
4
Order By: Relevance
“…The sensitivity of Xpert MTB in our study is 39.8% higher than the smear microscopy while in a study carried by Anwar sheed khan et al has shown a sensitivity 40-50% higher than microscopy technique. 15 Our study depicts the same results regarding sensitivity and specificity.…”
Section: Xpert Mtb In Pulmonary Tbsupporting
confidence: 78%
“…The sensitivity of Xpert MTB in our study is 39.8% higher than the smear microscopy while in a study carried by Anwar sheed khan et al has shown a sensitivity 40-50% higher than microscopy technique. 15 Our study depicts the same results regarding sensitivity and specificity.…”
Section: Xpert Mtb In Pulmonary Tbsupporting
confidence: 78%
“…Additionally, because of its low sensitivity, smear microscopy is often negative a few weeks into treatment when patients still have a significant mycobacterial load. 14…”
Section: Taking the Mbla Into Policy And Practicementioning
confidence: 99%
“…On the same hand, the significance of the economic impact on the livestock production sector is currently distributing tuberculosis, whereas TB prevalence increased with increasing people size and with farms having poor management of income [15][16][17][18]. And then this factor lead to the number of new cases of TB in 2017 was significantly higher than in 2013-2016 in Uganda [19], in Rwanda [20], in Kenya [21,22], especially, most of them are classified in high global TB burden countries [23] and others countries [24]. These infectious diseases not only occurred in Sub-Sahara but general are global, for example in 2013, there were 1.3 million AIDS mortalities in the top 30 countries representing 87% of global AIDS mortalities [25].…”
Section: Introductionmentioning
confidence: 99%